From exclusivism to tolerance: Religious moderation and the prevention of religious blasphemy in indonesia - Muhammad Fajar Noor Khamdani; Muhammad Royhan (Mishkat: Journal of Theology and Civilization, 2026)
Religious blasphemy remains a significant issue that may threaten social harmony and stability in Indonesia’s multicultural society. This study aims to analyze the role of religious moderation as a strategy for preventing religious blasphemy in Indonesia. The research employed a library research method using books, scholarly articles, and relevant documents, which were analyzed through a descriptive qualitative approach. The findings indicate that religious moderation plays a crucial role in preventing religious blasphemy by strengthening the values of balance, tolerance, justice, equality, and respect for religious diversity. A moderate religious attitude encourages individuals to maintain strong convictions in their own faith while refraining from degrading or rejecting other religions. The study also reveals that exclusivism, excessive truth claims, and a lack of appreciation for diversity are key factors contributing to religious blasphemy. This research contributes to the conceptual understanding of religious moderation as a preventive instrument for fostering a harmonious, peaceful, and tolerant society in Indonesia. Abstrak Penistaan agama masih menjadi persoalan yang berpotensi mengganggu kerukunan dan stabilitas sosial di Indonesia yang multikultural. Penelitian ini bertujuan menganalisis peran moderasi beragama sebagai strategi pencegahan penistaan agama di Indonesia. Penelitian menggunakan metode library research dengan sumber data berupa buku, artikel ilmiah, dan dokumen relevan yang dianalisis secara deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa moderasi beragama memiliki peran penting dalam mencegah penistaan agama melalui penguatan nilai keseimbangan, toleransi, keadilan, kesetaraan, dan penghormatan terhadap perbedaan keyakinan. Sikap moderat mendorong individu untuk tetap meyakini ajaran agamanya tanpa merendahkan atau menolak keberadaan agama lain. Temuan ini juga menunjukkan bahwa eksklusivisme, klaim kebenaran yang berlebihan, dan rendahnya penghargaan terhadap keberagaman merupakan faktor yang dapat memicu penistaan agama. Penelitian ini berkontribusi dalam memperkuat landasan konseptual mengenai pentingnya moderasi beragama sebagai instrumen preventif untuk membangun kehidupan masyarakat yang harmonis, damai, dan toleran di Indonesia.